A mixture of 15 phthalates and pesticides below individual chemical no observed adverse effect levels (NOAELs) produces reproductive tract malformations in the male rat. (November 2021) - Conley, Justin M.; Lambright, Christy S.; Evans, Nicola; Cardon, Mary; Medlock-Kakaley, Elizabeth; Wilson, Vickie S.; Gray, L. Earl
Highlights: Multiple molecular initiating events lead to adverse male reproductive development. Rat dams exposed to mixture of 9 phthalates, 5 pesticides, and 1 pesticide metabolite. Dose structure based on individual chemical NOAELs specific for male reproductive effects. Mixture produced numerous male reproductive adverse outcomes below chemical NOAELs. Cumulative assessment grouping should consider chemicals with common adverse outcomes. Abstract: Humans carry residues of multiple synthetic chemicals at any given point in time. Research has demonstrated that compounds with varying molecular initiating events (MIE) that disrupt common key events can act in concert to produce cumulative adverse effects. Congenital defects of the male reproductive tract are some of the most frequently diagnosed malformations in humans and chemical exposures in utero can produce these effects in laboratory animals and humans. Here, we hypothesized that in utero exposure to a mixture of pesticides and phthalates, each of which produce male reproductive tract defects individually, would produce cumulative effects even when each chemical is present at a no observed adverse effect level (NOAEL) specific for male reproductive effects. Pregnant Sprague-Dawley rats were exposed via oral gavage to a fixed-ratio dilution mixture of 5 pesticides (vinclozolin, linuron, procymidone, prochloraz, pyrifluquinazon), 1 pesticide metabolite (dichlorodiphenyldichloroethylene (DDE)), and 9 phthalates (dipentyl, dicyclohexyl, di-2-ethylhexyl, dibutyl, benzyl butyl, diisobutyl, diisoheptyl, dihexyl, and diheptyl) during the critical window of rat fetal masculinization (gestation day 14–18). The top dose (100% dose) contained each compound at a concentration 2-fold greater than the individual chemical NOAEL followed by a dilution series that represented each chemical at NOAEL, NOAEL/2, NOAEL/4, NOAEL/8, NOAEL/15, NOAEL/100, NOAEL/1000. Reduced fetal testis gene expression occurred at NOAEL/15, reduced fetal testis testosterone production occurred at NOAEL/8, reduced anogenital distance, increased nipple retention, and delayed puberty occurred at NOAEL/4, and severe effects including genital malformations and weight reductions in numerous reproductive tissues occurred at NOAEL/2. This study demonstrates that these phthalates and pesticides acted cumulatively to produce adverse effects at doses below which any individual chemical had been shown to produce an effect alone and even though they have different MIEs.